Stabilising the hip and pelvis during running: is there an explosive solution for uninjured athletes? - Meehan, D.; Williams, M.; Wilson, C.; Bradshaw, E. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
We compared the effectiveness of a conventional (slow-controlled) to a novel (explosive) eight week training program designed to improve lateral stability at the pelvis and hip during a running task. Parameters included: frontal-plane kinematics (500 Hz); electromyography recordings (1000 Hz) of gluteus medius (GM) and tensor fasciae latae (both sides); and oxygen kinetics. The groups were matched for hip and pelvis kinematics. After the training, reduction in peak angles at the hip and pelvis improved compared to baseline data regardless of group membership. Differences between groups were also found. Only the explosively trained group displayed changed GM onset times, where GM activation occurred earlier prior to ground contact when running. These differences in GM onsets support the notion of specific training adaptations, and the mechanism for hip and pelvis stability may not be the same for both groups. In addition, only the explosive group improved running performance (economy) further justifying this method of prescription.